A two-process model of metacognitive monitoring: Evidence for general accuracy and error factors. (August 2016) - Gutierrez, Antonio P.; Schraw, Gregory; Kuch, Fred; Richmond, Aaron S.
Abstract: We examined the latent structure of metacognitive monitoring judgments using hierarchical confirmatory factor analysis to compare five competing theoretical models with respect to domain-specific versus domain-general monitoring processes. We expected our results to support a domain-general monitoring model. Of the five models, the domain general monitoring model provided the best fit. In this model, level-1 domain-specific accuracy and error factors for each of the three tests loaded on second-order domain-general accuracy and error factors, which then loaded on a third-order general monitoring factor. This model suggest that metacognitive monitoring consists of two different types of cognitive processes, one that is associated with accurate monitoring judgments, and one that is associated with error in monitoring judgments. We discuss the theoretical and practical instructional implications of our findings. Highlights: Metacognitive processes are both domain-specific and domain general. Evidence suggests that there are separate general error and general accuracy factors. General error and general accuracy factors are subsumed by general monitoring.